Xanthotoxin prevents bone loss in ovariectomized mice through the inhibition of RANKL-induced osteoclastogenesis. Issue 7 (July 2016) - Dou, C.; Chen, Y.; Ding, N.; Li, N.; Jiang, H.; Zhao, C.; Kang, F.; Cao, Z.; Quan, H.; Luo, F.; Xu, J.; Dong, S.
Abstract Summary Xanthotoxin (XAT) is extracted from the seeds ofAmmi majus . Here, we reported that XAT has an inhibitory effect on osteoclastogenesis in vitro through the suppression of both receptor activator of nuclear factor-κB ligand (RANKL)-induced ROS generation and Ca2+ oscillations. In vivo studies showed that XAT treatment decreases the osteoclast number, prevents bone loss, and restores bone strength in ovariectomized mice. Introduction Excessive osteoclast formation and the resultant increase in bone resorption activity are key pathogenic factors of osteoporosis. In the present study, we have investigated the effects of XAT, a natural furanocoumarin, on the RANKL-mediated osteoclastogenesis in vitro and on ovariectomy-mediated bone loss in vivo. Methods Cytotoxicity of XAT was evaluated using bone marrow macrophages (BMMs). Osteoclast differentiation, formation, and fusion were assessed using the tartrate-resistant acid phosphatase (TRAP) stain, the actin cytoskeleton and focal adhesion (FAK) stain, and the fusion assay, respectively. Osteoclastic bone resorption was evaluated using the pit formation assay. Reactive oxygen species (ROS) generation and removal were evaluated using dichlorodihydrofluorescein diacetate (DCFH-DA). Ca2+ oscillations and their downstream signaling targets were then detected. The ovariectomized (OVX) mouse model was adopted for our in vivo studies. Results In vitro assays revealed that XAT inhibited the differentiation, formation, fusion, and bone resorption activity of osteoclasts. The inhibitory effect of XAT on osteoclastogenesis was associated with decreased intracellular ROS generation. XAT treatment also suppressed RANKL-induced Ca2+ oscillations and the activation of the resultant downstream calcium-CaMKK/PYK2 signaling. Through these two mechanisms, XAT downregulated the key osteoclastogenic factors nuclear factor of activated T cells c1 (NFATc1) and c-FOS. Our in vivo studies showed that XAT treatment decreases the osteoclast number, prevents bone loss, rescues bone microarchitecture, and restores bone strength in OVX mice. Conclusion Our findings indicate that XAT is protective against ovariectomy-mediated bone loss through the inhibition of RANKL-mediated osteoclastogenesis. Therefore, XAT may be considered to be a new therapeutic candidate for treating osteoporosis.